microRNA-630 Regulates Underglycosylated IgA1 Production in the Tonsils by Targeting TLR4 in IgA Nephropathy - Liu, Chan; Ye, Mu-Yao; Yan, Wen-Zhe; Peng, Xiao-Fei; He, Li-Yu; Peng, You-Ming (Frontiers in Immunology, 2020)
IgA nephropathy (IgAN) is the most common primary glomerular disease. The characteristic pathology involves immune complexes formed by the deposition of IgA1 and underglycosylated IgA1 aggregates in the mesangial area, which may be accompanied by the deposition of IgG and/or IgM and complement components. However, the molecular mechanisms of IgAN remain unclear. In the present study, microarray analysis showed that the expression of miR-630 was significantly reduced in palatal tonsils from IgAN patients compared with chronic tonsillitis. Additionally, bioinformatic analysis showed that Toll-like receptor 4 (TLR4) was the predicted target gene of miR-630 and was regulated by miR-630. When miR-630 was overexpressed in palatal tonsil mononuclear cells from IgAN patients, the expression of TLR4 was reduced and the content of IgA1 in the cell culture supernatant was decreased, and the level of galactosylation in the IgA1 hinge region was increased. Moreover, immunohistochemical analysis showed that the expression of TLR4 in IgAN patients was significantly increased and. After knocking down the expression of TLR4, both the concentration of IgA1 and the binding force of IgA1 with broad bean lectin were significantly reduced in IgAN. Furthermore, the mechanism study demonstrated that TLR4 might regulate the expression of IL-1β and IL-8 through NF-κB signaling pathway to modulate the concentration of IgA1 and the glycosylation level of IgA1. This interesting finding may offer new insight into the molecular mechanism of IgAN. Keywords: IgA nephropathy; palatal tonsils; miR-630; underglycosylated IgA1; TLR4